Effect of Lactate on the Microbial Community and Process Performance of an EBPR System - Rubio-Rincón, Francisco J.; Welles, Laurens; Lopez-Vazquez, Carlos M.; Abbas, Ben; van Loosdrecht, Mark C. M.; Brdjanovic, Damir (Frontiers in Microbiology, 2019)
Candidatus Accumulibacter phosphatis is in general presented as the dominant organism responsible for the biological removal of phosphorus in activated sludge wastewater treatment plants. Lab-scale enhanced biological phosphorus removal (EBPR) studies, usually use acetate as carbon source. However, the complexity of the carbon sources present in wastewater could allow other potential poly-phosphate accumulating organism (PAOs), such as putative fermentative PAOs (e.g. Tetrasphaera), to proliferate in coexistence or competition with Ca. Accumulibacter. This research assessed the effects of lactate on microbial selection and process performance of an EBPR lab-scale study. The addition of lactate resulted in the coexistence of Ca. Accumulibacter and Tetrasphaera in a single EBPR reactor. An increase in anaerobic glycogen consumption from 1.17 to 2.96 C-mol/L and anaerobic PHV formation from 0.44 to 0.87 PHV/PHA C-mol/C-mol corresponded to the increase in the influent lactate concentration. The dominant metabolism shifted from a polyphosphate-accumulating metabolism (PAM) to a glycogen accumulating metabolism (GAM) without EBPR activity. However, despite the GAM, traditional glycogen accumulating organisms (GAOs; Candidatus Competibacter phosphatis and Defluvicoccus) were not detected. Instead, the 16s RNA amplicon analysis showed that the genera Tetrasphaera was the dominant organism, while a quantification based on FISH-biovolume indicated that Ca. Accumulibacter remained the dominant organism, indicating certain discrepancies between these microbial analytical methods. Despite the discrepancies between these microbial analytical methods, neither Ca. Accumulibacter nor Tetrasphaera performed biological phosphorus removal by utilizing lactate as carbon source.